Effect of Polymers on the Physicochemical Properties and Biological Performance of Fenoprofen Calcium Dihydrate-Triacetyl-β-Cyclodextrin Complex - Hussein O. Ammar; Tarek S. Makram; Shaimaa Mosallam (MDPI AG, 2017)
Background: Fenoprofen calcium dehydrate (FCD) is counted as a non-steroidal, anti-inflammatory, anti-arthritic drug. FCD is slightly water soluble. It is indicated for mild pain relief, where the suggested dosage is 200 mg orally every 4 to 6 h. Aim: Reduce dissolution efficiency, reach an extended therapeutic effect and reduce the frequency of the drug side effects. Method: Combination of the co-evaporated drug:triacetyl-β-cyclodextrin complex prepared in a ratio of 1:3 and either of two polymers-hydroxylpropylmethyl cellulose (HPMC) or ethyl cellulose (EC)-in the same formulation. In vitro dissolution studies were carried in simulated gastric (pH 1.2) and intestinal (pH 6.8) fluids, by using the USP dissolution tester (rotating paddle apparatus). The FCD in vitro release from EC/drug complex was markedly retarded. Interaction between fenoprofen, TA-β-CD, EC, HPMC in the solid state were confirmed by FT-IR, DSC, XRD and SEM. In vivo studies assessed the anti-inflammatory and analgesic activities and the results were compared with the market product Nalfosab® Capsules. Results: Remarkable inhibition of inflammation and nociception after 24 h was attained for EC/drug complex. Conclusions: EC/drug complex has a sustained effect due to high remaining amount after elapsing with remarkable inhibition of inflammation.